G20210A Mutation in Prothrombin Gene and Risk of Myocardial Infarction, Stroke, and Venous Thrombosis in a Large Cohort of US Men - Ridker, Paul M.; Hennekens, Charles H.; Miletich, Joseph P. (Circulation (New York, N.Y.), 1999)
Background —A single base pair mutation in the prothrombin gene has recently been identified that is associated with increased prothrombin levels. Whether this mutation increases the risks of arterial and venous thrombosis among healthy individuals is controversial. Methods and Results —In a prospective cohort of 14 916 men, we determined the prevalence of the G20210A prothrombin gene variant in 833 men who subsequently developed myocardial infarction, stroke, or venous thrombosis (cases) and in 1774 age- and smoking status–matched men who remained free of thrombosis during a 10-year follow-up (control subjects). Gene sequencing was used to confirm mutation status in a subgroup of participants. Overall, carrier rates for the G20210A mutation were similar among case and control subjects; the relative risk of developing any thrombotic event in association with the 20210A allele was 1.05 (95% CI, 0.7 to 1.6; P =0.8). We observed no evidence of association between mutation and myocardial infarction (RR=0.8, P =0.4) or stroke (RR=1.1, P =0.8). For venous thrombosis, a modest nonsignificant increase in risk was observed (RR=1.7, P =0.08) that was smaller in magnitude than that associated with factor V Leiden (RR=3.0, P <0.001). Nine individuals carried both the prothrombin mutation and factor V Leiden (5 controls and 4 cases). One individual, a control subject, was homozygous for the prothrombin mutation. Conclusions —In a large cohort of US men, the G20210A prothrombin gene variant was not associated with increased risk of myocardial infarction or stroke. For venous thrombosis, risk estimates associated with the G20210A mutation were smaller in magnitude than risk estimates associated with factor V Leiden.